A Translation Analysis Of Adjective Clause In Sinister Movie And Its Subtitle - Yuliana, Reni, Dra. Dwi Haryanti, M.Hum, Drs. H. Djoko Srijono, M.Hum (2013)
The aims of this research are classifying translation shifts of adjective clause and describing the equivalence of translation in Sinister Movie and its Subtitle. The theory applies the descriptive research. The data of the research are English-Indonesian sentences containing the adjective clauses and its translation.The source of data is Sinister Movie.The method of collecting data is watching the film, underlying the adjective clause, writing the every sentence which contain adjective clause in SL and TL, and coding and classifying the data which contain the adjective clause. Data of the research are English of adjective clauses and its subtitle. Data source of the research is adjective clause find in the data source which is the Sinister movie and its subtitle. The technique of data analysis is (1) comparing the adjective clause with the Indonesian adjective clause. (2) analyzing English adjective clause and its subtitle. (3) analyzing the data of the research counts the percentage of each category, and (4) drawing conclusion and proposing the suggestion. The results of the research show that (1) adjective clauses that is translated into phrases is 20 data or 23% (2) adjective clause that is translated into noun clauses and adverb clauses that are 40 data or 34,7%, (3) adjective clause that is translated into clauses which uses the predicate in the form of phrases are 20 or 23%, (4) adjective clause that doesn't shift is 28 data or 24,3%, (5) adjective clause that is not translated is 1 datum or 1,7%.